2000
DOI: 10.1046/j.1439-0450.2000.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

The detection of proviral DNA by semi‐nested polymerase chain reaction and phylogenetic analysis of czech Maedi‐Visna Isolates Based ongagGene Sequences

Abstract: A semi-nested polymerase chain reaction (snPCR) for detecting proviral DNA of ovine lentivirus (OvLV) in peripheral blood mononuclear cells was developed. Primers for snPCR were situated within the gag gene of the Maedi-Visna virus (MVV) genome. A comparison between the snPCR and serological tests (agar gel immunodiffusion test, immunoblot) were performed using 98 ovine blood samples. Thirty (30.6%) of the 98 sheep examined had antibodies specific for the MVV. PCR showed 21 of them to be positive and nine sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
12
0
8
Order By: Relevance
“…These, particularly the samples positive in both assays, were not likely false-positives but most probably account for infected animals in which specific antibodies could not (yet) be detected. Several other studies with SRLV-PCRs reported seronegative animals that were found positive in PCR tests (Rimstad et al, 1993;Zanoni et al, 1996;Wagter et al, 1998;Celer et al, 2000). In addition, the results from the series of sequential samples from sheep with naturally acquired infections also clearly demonstrated this tendency.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These, particularly the samples positive in both assays, were not likely false-positives but most probably account for infected animals in which specific antibodies could not (yet) be detected. Several other studies with SRLV-PCRs reported seronegative animals that were found positive in PCR tests (Rimstad et al, 1993;Zanoni et al, 1996;Wagter et al, 1998;Celer et al, 2000). In addition, the results from the series of sequential samples from sheep with naturally acquired infections also clearly demonstrated this tendency.…”
Section: Discussionmentioning
confidence: 72%
“…Over the last decade several PCR assays for SRLV have been developed and published (Zanoni et al, 1992;Rosati et al, 1995;Wagter et al, 1998;Celer et al, 2000;Extramiana et al, 2002;Carrozza et al, 2003;Kuźmak et al, 2003;Álvarez et al, 2006;Eltahir et al, 2006;Gil et al, 2006;Leginagoikoa et al, 2006). The use of PCR in routine settings, however, is still limited because of the low sensitivity attained so far and the difficulties arising from the notorious genomic heterogeneity of the SRLV since lentiviruses are among the most rapidly evolving genomes (Blacklaws et al, 2004;Angelopoulou et al, 2005;De Andrés et al, 2005;Reina et al, 2006), which severely complicates the design of generally applicable oligonucleotides for priming and probing.…”
Section: Introductionmentioning
confidence: 99%
“…First virus isolation and partial genome characterisation of the Czech ovine lentivirus isolate OPM was published by Celer et al in 1997. Further six Czech ovine lentivirus isolates were characterised from snPCR products of amplification of partial gag gene sequences (Celer et al 2000), which confirmed the ovine lentivirus genotype in the Czech Republic is closely related to the prototype Maedi-Visna strains K1514 (Iceland), EV1 (Scotland) and SA-OMVV (South Africa), recently grouped to the A1 subgroup. Nevertheless, clear phylogenetic differences can be found between the six viruses analysed and the first OPM isolate.…”
mentioning
confidence: 83%
“…For years, numerous groups have attempted to establish PCR as a diagnostic method for SRLV infection, with variable results, such as the finding of amplicons in some seronegative animals and vice versa [20]. The former may represent animals before seroconversion [68,113], or longterm seronegative carriers, while the latter suggests that the PCR protocols may have lacked sensitivity.…”
Section: Pcrmentioning
confidence: 99%